2019
DOI: 10.21203/rs.2.10931/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bacterial contamination and antimicrobial susceptibility patterns of intensive care units medical equipment and inanimate surfaces at Ayder Comprehensive Specialized Hospital, Mekelle, Northern Ethiopia

Abstract: Objective: To determine bacterial contaminants and their antimicrobial susceptibility patterns from medical equipment and inanimate surfaces. Results: Of 130 swabs, 115(88.5%) were culture positive, of which contaminated medical equipment and inanimate surfaces account 70 (83.3%) and 45 (97.8%), respectively. From the culture positive swabs, a total of 154 bacterial isolates were identified, out of which 106 (68.8%) were gram-positive and 48 (31.2%) were gram negative. Most isolates (82%) were resistant to amp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
5
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 10 publications
(18 reference statements)
8
5
1
Order By: Relevance
“…Besides, susceptibility patterns exhibited by the isolates of Klebsiella sp. to amikacin and chloramphenicol were by and large similar to the results of earlier works [13,19]. Apart from Klebsiella sp., other Gram-negative bacilli such as Citrobacter sp., Salmonella sp., Enterobacter sp., E.coli, and Serratia sp., exhibited appreciable resistance against the same antibiotics.…”
Section: Antibiogramsupporting
confidence: 90%
See 4 more Smart Citations
“…Besides, susceptibility patterns exhibited by the isolates of Klebsiella sp. to amikacin and chloramphenicol were by and large similar to the results of earlier works [13,19]. Apart from Klebsiella sp., other Gram-negative bacilli such as Citrobacter sp., Salmonella sp., Enterobacter sp., E.coli, and Serratia sp., exhibited appreciable resistance against the same antibiotics.…”
Section: Antibiogramsupporting
confidence: 90%
“…Results revealed that in all the three wards, different patient-care equipments and inanimate objects directly or indirectly associated with patients were heavily contaminated by diverse species of bacterial pathogens. Of the total isolates, Gram-positive cocci were the most dominant as compared to the Gram-negative bacteria and were comparable to a number of studies reported from Ethiopia and Nigeria [11,13,14,19,23]. Nevertheless, in contrary to our results, previous studies reported that Gram-negative bacilli are the predominant isolates in hospital settings [7,18,24].…”
Section: Diversity Of Bacterial Isolatessupporting
confidence: 84%
See 3 more Smart Citations